Effects of Phyllanthus emblica extract on endothelial dysfunction and biomarkers of oxidative stress in patients with type 2 diabetes mellitus: a randomized, double-blind, controlled study - Usharani P (Dove Medical Press, 2013)
Pingali Usharani, Nishat Fatima, Nizampatnam Muralidhar Department of Clinical Pharmacology and Therapeutics, Nizam Institute of Medical Sciences, Panjagutta, Hyderabad, India Background: It has been reported that hyperglycemia can induce endothelial dysfunction via increased oxidative stress and that it plays a central role in the development of atherosclerosis and coronary heart disease. Phyllanthus emblica (Emblica officinalis, amla) is known for its antioxidant and antihyperlipidemic activity. The present study compared the effects of an aqueous extract of P. emblica (highly standardized by high-performance liquid chromatography to contain low molecular weight hydrolyzable tannins, ie, emblicanin A, emblicanin B, pedunculagin, and punigluconin) versus those of atorvastatin and placebo on endothelial dysfunction and biomarkers of oxidative stress in patients with type 2 diabetes. Methods: Eligible patients were randomized to receive either P. emblica 250 mg twice daily, P. emblica 500 mg twice daily, atorvastatin 10 mg in the evening and matching placebo in the morning, or placebo twice daily for 12 weeks. The primary efficacy parameter was the change in endothelial function identified on salbutamol challenge at baseline and after 12 weeks of treatment. Secondary efficacy parameters were changes in biomarkers of oxidative stress (malondialdehyde, nitric oxide, and glutathione), high sensitivity C-reactive protein levels, the lipid profile, and glycosylated hemoglobin (HbA1c) levels. Laboratory safety parameters were measured at baseline and after 12 weeks of treatment. Results: Eighty patients completed the study. Treatment with P. emblica 250 mg, P. emblica 500 mg, or atorvastatin 10 mg produced significant reductions in the reflection index (-2.25%±1.37% to -9.13%±2.56% versus -2.11%±0.98% to -10.04%±0.92% versus -2.68%±1.13% to -11.03%±3.93%, respectively), suggesting improvement in endothelial function after 12 weeks of treatment compared with baseline. There was a significant improvement in biomarkers of oxidative stress and systemic inflammation compared with baseline and placebo. Further, the treatments significantly improved the lipid profile and HbA1c levels compared with baseline and placebo. All treatments were well tolerated. Conclusion: Both atorvastatin and P. emblica significantly improved endothelial function and reduced biomarkers of oxidative stress and systemic inflammation in patients with type 2 diabetes mellitus, without any significant changes in laboratory safety parameters. Keywords: Phyllanthus emblica, atorvastatin, endothelial dysfunction, type 2 diabetes